Aircraft systems architecting: a functional-logical domain perspective - Guenov, Marin D.; Molina-Cristobal, Arturo; Voloshin, V.; Riaz, Atif; van Heerden, Albert S. J.; Sharma, Sanjiv; Cuiller, C.; Giese, Tim (AIAA, 2016)
Presented is a novel framework for early systems architecture design. The framework defines data structures and algorithms that enable the systems architect to operate interactively and simultaneously in both the functional and logical domains. A prototype software tool, called AirCADia Architect, was implemented, which allowed the framework to be evaluated by practicing aircraft systems architects. The evaluation confirmed that, on the whole, the approach enables the architects to effectively express their creative ideas when synthesizing new architectures while still retaining control over the process.